Results 2013 - Banque mondiale (Springer, 2015)
The World Bank's Results 2013 provides the Bank's shareholders, partners, and external stakeholders with an integrated view of results and performance in recent years. It covers the World Bank and reports on aggregate results that countries have achieved with Bank support against the backdrop of global development results. The report also asseses the Bank's operational and organizational performance at the corporate.